Estimasi Cadangan Karbon Tegakan Mangrove di Lombok Barat, Nusa Tenggara Barat - Lestariningsih, Wiwid Andriyani; Himawan, Mahardika Rizqi; Siagian, Raja Aditya Sahala; Majerus, Kara Muriel Angela; Putra, Brilliant Rudzaky Ridwan; Anggereni, Aprilia; Buhari, Nurliah (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2024)
Mangrove ecosystems are a vital form of aquatic ecosystem that significantly contribute to maintaining carbon balance in the atmosphere and support climate change mitigation efforts. Their ability to absorb and store carbon in both biomass and soil makes them among the most effective carbon sinks. This study aims to estimate the carbon storage of mangrove stands in the Gita Nada Mangrove Area, Sekotong, West Lombok. The research was conducted at three stations: Station 1 (Berambang), Station 2 (Siung), and Station 3 (Bangko-Bangko). Data collection involved a 10 x 10 meter transect, where species and diameter at breast height (DBH) data were recorded. Allometric equations were then applied to calculate biomass and carbon reserve values. The results identified four mangrove species: Rhizophora mucronata, R. stylosa, R. apiculata, and Avicennia marina. The average mangrove density at each station fell within the moderate to dense category, with values ranging from 1000 to 4666.66 individuals per hectare. The estimated carbon stocks of the mangrove stands were as follows: Station 1 had 149.33 tons per hectare, Station 2 had 28.38 tons per hectare, and Station 3 had 476.36 tons per hectare. These findings indicate significant differences in estimated carbon stock values across the stations. Overall, the results of this study provide crucial information to support conservation and restoration efforts for mangrove ecosystems in West Lombok, enhancing understanding of the role of mangroves in mitigating climate change.